When Policy Meets Public Distrust: A Social Network Analysis on Indonesia's MBG Program - Fauziah, Rizky, Dr; Barus, Rehia Karenina Isabella, Dr.; Dwiana, Ressi, Dr. (JURNAL KOMUNIKASI INDONESIA, 2026)
The Indonesian government program Free Nutritious Meal, locally abbreviated as MBG, launched in early 2025, has generated significant public controversy. Data from the Institute for Development of Economics and Finance (INDEF) indicate that, as of August 2025, approximately 4,000 students across Indonesia had reportedly suffered food poisoning associated with the program. This situation has fueled widespread public concern and contributed to declining trust in government. This study aims to analyze communication networks surrounding the MBG on the social media platform X. This study draws on Trust and Distrust Theory and employs a Social Network Analysis (SNA) approach to examine how public distrust is formed and disseminated through communication networks on X. Data was collected using NodeXL to map and evaluate the structure of communication networks formed around the issue. The data revealed that between May 1 and August 31, 2025, a total of 520 users engaged in discussions on X, generating 675 communication network edges. Sentiment analysis further demonstrated that public perceptions of the MBG program were predominantly negative (50%), while 24% posts expressed positive sentiments and 26% were neutral. The findings suggest that ineffective government communication emerged as a key factor contributing to the heightened level of public distrust regarding the long-term viability of the MBG program. Theoretically, this study extends Trust and Distrust Theory by showing that public distrust is shaped not only by negative evaluations but also by networked interactions, actor centrality, and the circulation of negative narratives.